2001
DOI: 10.1021/ie001115e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modelling of the Transformation of Aqueous Ethanol into Hydrocarbons on a HZSM-5 Zeolite

Abstract: A kinetic model for the transformation of aqueous ethanol into hydrocarbons on a HZSM-5 zeolite has been proposed for the 623−723 K range on the basis of experiments carried out in an isothermal fixed-bed reactor with feeds of ethene, ethanol−water mixtures of different mass ratios, and diethyl ether. The kinetic model is of interest for directly upgrading the liquid product obtained by the fermentation of carbohydrate wastes. It is based on the latest progress made in the catalytic transformation of methanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 43 publications
4
69
1
Order By: Relevance
“…1-4, and a favorable effect of attenuating the deactivation by coke. This fact has been previously observed for the transformation of bio-ethanol into hydrocarbons, 22,24,34 and it is a key factor for controlling the deactivation in the transformation of other oxygenates into hydrocarbons, such as methanol and the bio-oil obtained from pyrolysis of lignocellulosic biomass. [35][36][37] The moderation of the acid strength of the sites caused by hydration and the competition of water with hydrocarbons (coke precursors in the deactivation) in their adsorption on the acid sites explain the attenuation in the reaction rates of the steps caused by water.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…1-4, and a favorable effect of attenuating the deactivation by coke. This fact has been previously observed for the transformation of bio-ethanol into hydrocarbons, 22,24,34 and it is a key factor for controlling the deactivation in the transformation of other oxygenates into hydrocarbons, such as methanol and the bio-oil obtained from pyrolysis of lignocellulosic biomass. [35][36][37] The moderation of the acid strength of the sites caused by hydration and the competition of water with hydrocarbons (coke precursors in the deactivation) in their adsorption on the acid sites explain the attenuation in the reaction rates of the steps caused by water.…”
mentioning
confidence: 58%
“…Accordingly, the HZSM-5 zeolite is effective below 300 C and has been used with different modifications aimed at moderating its acid strength to avoid secondary reactions of ethylene conversion and to attenuate coke formation. [16][17][18][19][20] However, propylene and butene production takes place by transformation of ethylene through a oligomerization-cracking mechanism that requires temperatures above 350 C. [21][22][23] The main difficulty of this process is catalyst deactivation, although a distinction must be made between reversible deactivation (due to coke deposition) and the zeolite irreversible deactivation due to water content in the reaction medium (dealuminization). 24 In a previous study, the good performance of a catalyst based on a HZSM-5 zeolite treated with 0.2 M NaOH solution for 10 min has been proven.…”
Section: Introductionmentioning
confidence: 99%
“…This includes, among others, the investigation of different topologies [41], metal modification [42,43], framework modification [44,45] and phosphorus introduction [46]. Furthermore, the reaction mechanism of ethanol conversion to hydrocarbons is still a matter of debate [47][48][49]. In addition to the complexity brought about by a multitude of post synthesis modifications methods, the assessment of reported catalyst performance in ethanol conversion is often challenging because of the large variety of reaction conditions employed and catalyst properties investigated.…”
Section: Case Study: Ethanol Conversion To Hydrocarbonsmentioning
confidence: 99%
“…Production of hydrocarbons from ethanol using catalysts has been reported by many researchers [1][2][3][4][5][6][7][8][9]. In most cases, H-ZSM-5 zeolite was used as a catalyst [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, H-ZSM-5 zeolite was used as a catalyst [1][2][3][4]. Saha et al reported ethanol conversion using Zn-and Ga-doped ZSM-5 zeolite catalysts [5].…”
Section: Introductionmentioning
confidence: 99%